Interpretación democrática de la constitución colombiana en tiempos de crisis (pandemia COVID-19) / Democratic interpretation of the Colombian Constitution in times of crisis (COVID-19 pandemic) - CHACÍN FUENMAYOR, Ronald; VILLA-VILLA, Sandra; BERROCAL-DURAN, Juan Carlos (Utopía y Praxis Latinoamericana, 2020)
RESUMENSe explican las implicaciones de la pandemia del COVID-2019, la crisis que ha generado y sus efectos graves en la salud pública, en las esferas: social, política, económica y jurídica. Con respecto a este aspecto, se describe el manejo de la crisis del COVID-2019 en Colombia, mediante el análisis de las actuaciones de los poderes públicos, a los fines de determinar si la Constitución Política se ha interpretado conforme al régimen democrático en ella establecido. La metodología consistió en una indagación documental sobre las actuaciones de los órganos políticos y jurisdiccionales que han regulado la crisis social del COVID-2019.ABSTRACTThe implications of the COVID-2019 pandemic, the crisis it has generated and its serious effects on public health are explained in the social, political, economic and legal areas. With regard to this aspect, the management of the of COVID-2019 crisis in Colombia is described, through the analysis of the actions of the public powers, in order to determine whether the Political Constitution has been interpreted in accordance with the democratic regime established. The methodology consisted of a documentary inquiry into the actions of the political and jurisdictional bodies that have regulated the COVID-2019 social crisis.